Pengembangan Bahan Ajar Pada Pembelajaran IPS Sub-SubTema Interaksi Manusia Dengan Lingkungan Alam Untuk Siswa Kelas VII SMP Negeri 2 Banyudono - Mustafida, Laila Dyah; , Drs. Suharjo, M.S (2015)
This research includes the study of quantitative and qualitative methods of research and development (Research and Development). The model used is the development of 4D (Define, Design, Development and Dissemination). Quantitative and qualitative research emphasizes the analysis of numerical data are processed with statistical methods and analyzed in form descriptive. Research and development is the research methods used to produce a particular product, and test the effectiveness of the product. This research aim to identify teaching materials Curriculum 2013 issue of Ministry of Education and Culture in class VII SMP, and produce the feasibility of teaching materials on learning ips sub-themes of human interaction with the natural environment according to the response matter experts, expert teaching materials, teachers and students, as well as to determine the effectiveness of the development of teaching materials teaching materials IPS class VII SMP Negeri 2 Banyudono. The results showed that: (1) Development of teaching materials seventh grade social studies curriculum in 2013 published by the Ministry of Education and Culture sub-sub-theme of human interaction with the natural environment such errors occur is a language, an explanation of material, sentence, writing resources, kalilmat less complete and clear, the use of Akata, too many concepts, which are not accompanied by a cause and effect, and the picture is less clear and there is no explanation. (2) According to validation matter experts and expert teaching materials teaching materials worth of products used in the learning process in terms of feasibility aspects of content, presentation aspects, aspects of language and aspects kegrafikan with persetase actual score 78% for the category of "very appropriate" and a score of 75% for the category of "Match". (3) Based on the results of Paired t test showed that there are differences in the experimental class with the controls. Judging from the increase in the experimental class lessons were higher at 12.51%. Compared with the control class value of 9.5%.